Penerapan Algoritma Skipjack Untuk Menyandikan Short Message Service - Sinaga, Nurainun; Aini, Syarifah; Gulo, Bezatulo (STIKOM Tunas Bangsa Pematangsiantar, 2018)
The security and confidentiality of Short Message Service (SMS) is very important for senders and recipients of messages. Generally, SMS is displayed in plain text form which can make it easy for the cryptanalyst to skipjack the message to be distributed. SMS security can be done by encrypting it based on one of the cryptographic algorithms in order to maintain the authenticity and security of messages and can make it difficult for others to know the original meaning of the SMS. Skipjack algorithm is one of cryptography algorithm that can be used for SMS encoding. The Skipjack algorithm is an electronic 64-bit codebook algorithm that converts 64-bit blocks into 64-bit blocks of output. The parameter used for encryption is 80-bit key and has 32 rounds of the encryption process and description. This study describes how SMS text encoding based on skipjack algorithm with the purpose of distributed SMS can be guaranteed to be safe and avoid misuse.